2020
DOI: 10.1029/2019jd032260
|View full text |Cite
|
Sign up to set email alerts
|

Inertia‐Gravity Waves Revealed in Radiosonde Data at Jang Bogo Station, Antarctica (74°37′S, 164°13′E): 2. Potential Sources and Their Relation to Inertia‐Gravity Waves

Abstract: Potential sources of inertia‐gravity waves (IGWs) in the lower stratosphere (z = 15–22 km) at Jang Bogo Station, Antarctica (74°37′S, 164°13′E) are investigated using 3‐year (December 2014 to November 2017) radiosonde data, including the 25‐month result (December 2014 to December 2016) analyzed in Yoo et al. (2018, https://doi.org/10.1029/2018JD029164, Part 1). For this investigation, three‐dimensional backward ray tracing calculations are conducted using the Gravity wave Regional Or Global RAy Tracer. Among 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 90 publications
1
13
0
Order By: Relevance
“…The intrinsic frequency is distributed between 2.2 and 5.8 f in the troposphere and 1.8–3.2 f in the stratosphere. It should be noted that when calculating the vertical wave number, the weighted average will lead to a narrow range of vertical wavelengths, which is also consistent with the results using similar method for the calculation of vertical wave number (Wang et al., 2005; Yoo et al., 2020). However, as the vertical wavelengths are limited by the radiosonde data and calculation method, only relatively short vertical wavelengths with narrow width are discussed in this study.…”
Section: Resultssupporting
confidence: 86%
“…The intrinsic frequency is distributed between 2.2 and 5.8 f in the troposphere and 1.8–3.2 f in the stratosphere. It should be noted that when calculating the vertical wave number, the weighted average will lead to a narrow range of vertical wavelengths, which is also consistent with the results using similar method for the calculation of vertical wave number (Wang et al., 2005; Yoo et al., 2020). However, as the vertical wavelengths are limited by the radiosonde data and calculation method, only relatively short vertical wavelengths with narrow width are discussed in this study.…”
Section: Resultssupporting
confidence: 86%
“…Based on the observed wind and temperature profiles, the Stokes‐parameter method can analyze polychromatic wave perturbations (Eckermann, 1996; Eckermann & Vincent, 1989), while the hodograph technique can provide in detail the wave parameter estimate of monochromatic inertia‐GWs (IGWs) perturbations and is extensively used to investigate the IGW activity from various observation data. By means of the hodograph technique, the seasonal and latitudinal variations of IGW parameters in the troposphere and low stratosphere (TLS) are widely studied from the radiosonde observations (e.g., Gong & Geller, 2010; Huang et al., 2018; Moffat‐Griffin et al., 2020; Murphy et al., 2014; Tsuda et al., 1994; Vincent & Alexander, 2000; Yamamori & Sato, 2006; Yoo et al., 2020; Zhang & Yi, 2007). In general, the intrinsic frequency of IGWs increases with increasing latitude, while the ratio of intrinsic frequency to inertia frequency and dominant horizontal and vertical wavelengths decrease slightly with increasing latitude (Alexander et al., 2002; Wang et al., 2005; Zhang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to tropospheric jets accompanied by frontal systems, the polar night jet in the stratosphere has also been considered to be an important source for GWs. Several observational studies have revealed enhanced GW activities near the stratospheric polar night jet using lidar (Whiteway et al., 1997), radiosonde (Sato & Yoshiki, 2008; Yoo et al., 2020, 2018; Yoshiki et al., 2004; Yoshiki & Sato, 2000), and satellite (Ern et al., 2011; Schroeder et al., 2009; Wu & Zhang, 2004), and strong GW activities have been observed mainly at the edge of the polar vortex (Whiteway et al., 1997; Yoshiki et al., 2004). Given that the edge of the vortex is often located near KSS, the polar night jet in the stratosphere could be an important source of GWs in the upper mesosphere over KSS.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of GWs from the jet stream can be related to the imbalance of the large-scale flow associated with the tropospheric jet stream. In order to diagnose the imbalance, the residual of the nonlinear balance equation (RNBE) has been employed (Hertzog et al, 2001;Moore & Abeling, 1988;Yoo et al, 2020;Zhang et al, 2000Zhang et al, , 2001. In addition to tropospheric jets accompanied by frontal systems, the polar night jet in the stratosphere has also been considered to be an important source for GWs.…”
mentioning
confidence: 99%